2013
DOI: 10.1155/2013/418742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Environmental Stimuli upon the Human Body in Winter Outdoor Thermal Environment

Abstract: In order to manage the outdoor thermal environment with regard to human health and the environmental impact of waste heat, quantitative evaluations are indispensable. It is necessary to use a thermal environment evaluation index. The purpose of this paper is to clarify the relationship between the psychological thermal responses of the human body and winter outdoor thermal environment variables. Subjective experiments were conducted in the winter outdoor environment. Environmental factors and human psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…ETFe can evaluate the effect of different postures on behavioral thermoregulation in outdoor spaces. Furthermore, verification experiments have been carried out to confirm the relation between ETFe and the physiological and psychological effects on the human body, and its effectiveness as an outdoor environment evaluation factor, including heat conduction from the ground for an outdoor space, has been confirmed [11]. In these verification experiments, heat transfer and short-wave solar radiation were shown to have as great effect an as environmental factors which contribute to the ETF.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…ETFe can evaluate the effect of different postures on behavioral thermoregulation in outdoor spaces. Furthermore, verification experiments have been carried out to confirm the relation between ETFe and the physiological and psychological effects on the human body, and its effectiveness as an outdoor environment evaluation factor, including heat conduction from the ground for an outdoor space, has been confirmed [11]. In these verification experiments, heat transfer and short-wave solar radiation were shown to have as great effect an as environmental factors which contribute to the ETF.…”
Section: Introductionmentioning
confidence: 92%
“…As the behavioral thermoregulation model in this study is an improved Two-Node Model [17,47]. Therefore, this model does not assume that the thermal neutral temperature is much lower than the thermal environment for an indoor environment, the difference with the actual value in a low temperature environment in which the blood vessel contraction coefficient is small, is considered to be large.…”
Section: Relationship Between Etfe and Mean Skin Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that solar radiation affects the thermal sensory perceptions of the human body in an outdoor space [1]- [8]. In addition, it has been demonstrated that the effects of direct and reflected solar radiation are significant in an outdoor space.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the outdoor thermal environment has a strong effect on the thermal and comfort sensations of the human body [9] [10] [11]. It has furthermore been demonstrated that short-wavelength solar radiation becomes significantly stronger as a factor that impacts the thermal environment evaluation index in an outdoor space [7] [8]. According to the effect of albedo, a road surface can become heated to the degree whereby it cannot be touched directly, and sensational and physiological temperature increases.…”
Section: Introductionmentioning
confidence: 99%